El linchamiento mediático, en la Ley De Comunicación Ecuatoriana - Monar Bosquez, Jorge Regulo (2016)
In the following thesis called "The media lynching, IN THE LAW OF COMMUNICATION ECUATORIANA" I conducted an assessment of the problems arising in society and the media since the new law took effect. Iniciare to a study some principles and constitutional rights. In the form of overview it has been taken into account The Communications Law, the Code of Criminal Integral, Ecuadorian Civil Code, human rights, the media lynching as well as a comparative study of the legislation of Ecuador with other countries. Then I review the opinion of representatives of the Ecuadorian Academy of Language, some writers, and various bodies and means at national and international level, on freedom of expression and media lynching, to support the proposal to repeal this legal figure in Law Organic Communication, in order to guarantee people the right to freedom of expression guaranteed in the Constitution. To meet the goals, I have conducted a field study based on surveys and interviews aimed at journalists and lawyers in Free Exercise, as well as authorities. Among the conclusions and recommendations, to finish the tabulation of surveys and interviews, it is clearly noted that respondents and interviewees share majority, the media lynching violates freedom of expression to produce self-censorship and that the best would be repealed. As clear evidence that the issues raised generates social discomfort, has presented the conclusions and recommendations drawn from the views expressed on the questions raised in the surveys and interviews, applied to individuals involved in performing the respective fieldwork